Evaluating Remediation Techniques for Fouled Ballast on Army Installations - Charles E. Williams; Thomas J. Beasley (Engineering Proceedings, 2023)
Rail transport is a vital asset for U.S. Army distribution networks for movements of oversized and overweight vehicles and munitions. As the rail infrastructure ages on military installations, the reliability of these rail systems is a critical concern to support military power projection requirements. The Engineering Research and Development Center (ERDC) evaluates over 1500 miles of Army track approximately every four years. Many Army installations have significant problems with fouled ballast. These installations have few resources to remediate fouled ballast, and/or may not be aware of remediation techniques. The primary objective of this paper is to provide a list of remediation techniques for installations to implement with efforts to reduce fouled ballast and improve track maintenance.